AB0486 High frequency ultrasound and laser doppler flowmetry for the evaluation of digital dermal thickness and fingertip blood perfusion in systemic sclerosis patients. (23rd January 2014) - Sulli, A.; Ruaro, B.; Alessandri, E.; Ravera, F.; Cimmino, M. A.; Zampogna, G.; Cutolo, M.
Abstract : Background: Modified Rodnan skin score (mRss) and high frequency ultrasound (US) are employed to evaluate dermal thickness (DT) in systemic sclerosis (SSc) patients (1 -3 ). Laser Doppler flowmetry (LDF) is used to assess and measure the peripheral blood perfusion (4 ). Objectives: The aim of this study was to identify possible correlations between finger dermal thickness (DT) using both US and mRss, and fingertip blood perfusion (FBP) in SSc patients. Methods: Forty-nine consecutive SSc patients and 37 healthy subjects (CNT) were enrolled, after informed consent. US was performed in both SSc patients and CNT to evaluate DT (ultrasound-DT) at the level of the dorsum of the middle phalanx of the third finger on both right and left hand, and the average value was recorded in millimetres. After double blind evaluation of US pictures, the intra-operator reproducibility in measuring DT was found of 95%. DT was also assessed by mRss in SSc patients at the level of the dorsum of the fingers bilaterally, and the average score of the fingers was calculated. LDF was performed in both SSc patients and CNT. FBP was detected at the level of the fingertips bilaterally, and the results were expressed as perfusion units (PU). The same operator (BR) performed the examination, and there was a 88% reproducibility of the LDF assessment. Statistical analysis was carried out by non parametric tests. Results: SSc patients showed higher ultrasound-DT as well as lower FBP at the level of the fingers, than healthy subjects (p<0.0001). A negative correlation was observed between FBP and both ultrasound-DT (r=-0.36, p=0.02) and mRss values (r=-0.41, p=0.002). A positive statistically significant correlation was observed between left and right finger ultrasound-DT (r=0.68, p<0.0001), as well as between ultrasound-DT and mRss (r=0.55, p<0.0001). Conclusions: A significant negative correlation between finger DT, evaluated by either US or mRss, and FBP, evaluated by LDF, is detectable with reliability in SSc patients. References: Clements PJ, et al. J Rheumatol 1993; 20: 1892-6. Moore TL, et al. Rheumatology 2003; 42: 1559-63. Kaloudi O et al. Ann Rheum Dis. 2010; 69:1140-3. Cutolo M, et al. J Rheumatol 2010; 37:1174-80. Disclosure of Interest: None Declared